Significantly enhanced thermoelectric properties of p-type Mg3Sb2 via co-doping of Na and Zn. (15th January 2018) - Ren, Zhensong; Shuai, Jing; Mao, Jun; Zhu, Qing; Song, Shaowei; Ni, Yizhou; Chen, Shuo
Abstract: The effects of co-doping Na and Zn into thermoelectric Mg3 Sb2 were investigated. Na was found to be a very effective hole dopant in our previous study. However, the lattice thermal conductivity noticeably increases limiting further improvement of the figure of merit. Here, we show that isoelectronic Zn doping weakens the polar covalent bonding and ionized impurity scattering and leads to a 3 fold increase of carrier mobility. Lattice thermal conductivity, due to the introduced ionic mass contrast between Zn 2+ and Mg 2+, is supressed significantly especially at lower temperature range between 300 K and 450 K. The indicator of the average performance, the ( PF )eng (engineering power factor) and ( ZT )eng (engineering ZT ), were showed ∼50% and ∼76% improvement, respectively. The same strategy of co-doping two different elements with different functions could also be applied to other thermoelectric Zintl compounds typically with low carrier concentration and carrier mobility for even higher thermoelectric properties. Graphical abstract: Co-doping Na and Zn into thermoelectric compound Mg 3 Sb 2 simultaneously improves all the thermoelectric transport properties, electrical conductivity σ, Seebeck coefficient S and reduced thermal conductivity κ, thus leading to significantly higher ZT of ∼0.8 at 773 K, a 33 % improvement. Importantly, greatly improved power factor in the whole measured temperature range, i.e., 300% at 323 K and 15% at 773 K, respectively, leads to not only the highest average power factor but also the highest output power density for p-type Mg3 Sb2 . Image 1